1974
DOI: 10.1037/h0037335
|View full text |Cite
|
Sign up to set email alerts
|

Organizational commitment, job satisfaction, and turnover among psychiatric technicians.

Abstract: This investigation studied changes across time in measures of organizational commitment and job satisfaction, as each related to subsequent turnover among a sample of recently employed psychiatric technician trainees. A longitudinal study across a lOi-month period was conducted, with attitude measures collected at four points in time. The results of a discriminant analysis indicate that significant relationships existed between certain attitudes held by employees and turnover. Relationships between attitudes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
2,486
3
171

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 4,063 publications
(2,844 citation statements)
references
References 28 publications
54
2,486
3
171
Order By: Relevance
“…This paper also employed the most commonly adopted measurement of organizational commitment [50] to assess the commitment level of our sampled family employees. For each of the 15 items included, one family employee was asked to rate their opinion in a 5-point Likert scale (1 = "strongly disagree" and 5 = "strongly agree").…”
Section: B Measurement Of Variablesmentioning
confidence: 99%
“…This paper also employed the most commonly adopted measurement of organizational commitment [50] to assess the commitment level of our sampled family employees. For each of the 15 items included, one family employee was asked to rate their opinion in a 5-point Likert scale (1 = "strongly disagree" and 5 = "strongly agree").…”
Section: B Measurement Of Variablesmentioning
confidence: 99%
“…Maintaining commitment during the uncertainty that is associated with the transition period is very important because it changes an internal part of organisational culture (Narine & Persaud, 2003). Furthermore, (Porter, et al, 1974) argued that organisational commitment starts with a firm belief in the acceptance of the organisation's goal and values and additionally the authors suggested that the internalization of organisational values should create a strong belief in these values, consequently creating a perception of individual commitment to the organisation. Likewise, Ritchie (2000) mentioned that commitment is an essential outcome of internalization, as it helps ensure a stable population that is likely to maintain and continue the culture and further to that, it was found that employees with a positive predilection and belief about change will enhance a firm's capability to change (Lau, Tse, & Zhou, 2002;Tripsas & Gavetti, 2000).…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Porter, Steers, Mowday, and Boulian (1974) defined organisational commitment as "the relative strength of an individual's identification with and involvement in a particular organisation." Organisational commitment can be divided into two concepts; behaviour and attitude (Johnston, Parasuraman, Furell, & Black, 1990).…”
Section: Commitment To Changementioning
confidence: 99%
“…Commitment is the strength of employees' identification with and involvement in their organizations (Porter, Steers, Mowday, & Boulian, 1974). Buchanan (1974) describes commitment as "…a partisan affective attachment to the goals and values of an organization, to one's roles in relation to the goals and values, and to the organization for its own sake, apart from its purely instrumental worth" (p. 53).…”
Section: Onimentioning
confidence: 99%